I accuse and "i wander": on the writer's identity formation from the SDGS perspective - Weizhou, Wang; Bee, Lim Choon; Ser, Wue Hiong (Brazilian Journals, 2024)
Objective: The objective of this study is to investigate the definition of writers, exploring the different configurations of writers in the context of diverse education, and learning about the importance of quality education for independent thinking and critical thinking. Method: This research adopts the methods of literature research and close reading of texts, analyzing historical works, academic monographs, and literary works to summarize the experiences, creations, and identities of contemporary Chinese writers, forming a comprehensive perspective. Results and Discussion: The writer is not only the material individual but also the creation main body, its position and the function in the literature field hold the balance. They are the primary force of literary production and the core of literary mechanism. After analyzing the history, definition and identity of a writer, we can divide the writer's identity into two types: the intellectual and the wanderer, which to some extent clears the fog of the writer's identity. Originality/Value: The current academic attention to the writer's identity is insufficient, the writer's identity structure in literary research is still not clear. This has led to a divergence of views in the community and the academic community on the writer, almost all the discussions are in disputes and conflicts, and the writer's identity which is very vague is more complicated. This study clarifies the definition of writers, provides a clearer definition and conclusion on the identity configuration of writers, and highlights the importance of quality education for independent and critical thinking.